Corporate Tax Responsibility: Analysis of the Role of Companies in Promoting Sustainable Tax Behavior - Firanda, Irfan; Diantimala, Yossi; Meutia, Rita (International Journal of Economics, Business Management and Accounting (IJEBMA), 2025)
This study aims to analyze Corporate Tax Responsibility (CTR) in Indonesia, specifically how companies disclose tax-related information in their reports. This study focuses on a qualitative content analysis of annual reports and financial statements of companies in Indonesia that have reported their finances using eXtensible Business Reporting Language (XBRL) to the Indonesia Stock Exchange (IDX) and the Directorate General of Taxes (DGT) from 2019 to 2023. The results of the study indicate that Indonesian companies are increasingly aware of their role in the national tax system. It was found that the phrase “Tax Policy” appeared most frequently in the reports, followed by “Tax Reconciliation” and “Effective Tax Rate,” which were consistently disclosed. In conclusion, companies in Indonesia largely comply with mandatory reporting requirements and provide technical details in their financial notes. This study recommends that companies provide a more comprehensive narrative about their tax policies and governance